PB DIFFUSION IN CLINOPYROXENE - Cherniak D.J. (My University, 1998)
Chemical diffusion of Pb under anhydrous, pO2-buffered conditions has been measured in natural clinopyroxenes of two different compositions: one a near-end-member diopside and the other of more iron-rich composition (~40% diopside component). The sources of diffusant were fused and finely ground mixtures of PbS powder and ground pyroxene. Experiments were run in sealed silica glass capsules with a solid buffer (to buffer at QFM). Rutherford backscattering spectrometry (RBS) was used to measure diffusion profiles. The following Arrhenius parameters were obtained for diffusion normal to (110) over the temperature range 800-1100°C under QFM-buffered conditions: D=4.03x102exp(-544+/-40 kJ mol-1/RT) m2 s-1 (for Di95) D=2.20x10-4exp(-387+/-31 kJ mol-1/RT) m2 s-1 (for Di40). Diffusion in the more iron-rich clinopyroxene is faster and activation energy for diffusion lower than that for the near-end-member diopside. Little dependence of Pb diffusion on crystallographic orientation was noted in diopside. Diffusion of Pb is comparable to that of Sr in natural diopside, but faster than many other species in clinopyroxenes. The activation energy for Pb diffusion in diopside is relatively high and Pb diffusivities are fairly slow when compared with the extant diffusion data for other minerals. It follows as consequence of these relatively slow diffusivities that Pb closure temperatures are higher in diopside than for most other minerals, with the exception of a few phases such as zircon and garnet. The faster diffusivities that characterize Fe-rich clinopyroxenes will lead to somewhat depressed closure temperatures, but clinopyroxenes in general should be fairly retentive of Pb isotopic information when subjected to all but the most extreme thermal events.
Keywords: DIFFUSION; PB; CLINOPYROXENES